The Concept of Deliberation in the Qur’an as an Ethical Basis for Decision-Making in Library Management - Ayu Trysnawati; Sohrah Sohrah; Rosmini Rosmini (Inkunabula: Journal of Library Science and Islamic Information, 2026)
Decision-making in library management tends to be oriented towards administrative and efficienct aspects, while the ethical dimension has not been formulated conceptually. This study aims to reconstruct the concept of deliberation in the Qur'an as an ethical basis for library decision-making. The study uses a qualitative approach with a library study design. Data were obtained from contemporary exegetical literature, particularly the thoughts of M. Quraish Shihab and Yusuf al-Qaradawi, as well as scientific articles searched through Google Scholar with the keyword deliberation, organizational ethics, and library management, which were limited to publications in the last five years. The analysis was conducted using thematic analysis techniques to identify normative values ​​and their relevance in an institutional context. The results show that deliberation contains the principles of inclusive participation, deliberative justice, trustworthiness, and collective responsibility that can be operationalized in program planning, collection development, and service evaluation. This study contributes theoretically by formulating deliberation as an ethical framework for organizations based on Islamic values and practically provides a normative foundation for participatory and accountable library governance. Abstrak Pengambilan keputusan dalam manajemen perpustakaan cenderung berorientasi pada aspek administratif dan efisiensi, sementara dimensi etika belum dirumuskan secara konseptual. Penelitian ini bertujuan untuk merekonstruksi konsep musyawarah dalam Al-Qur'an sebagai landasan etis bagi pengambilan keputusan di perpustakaan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kepustakaan. Data diperoleh dari literatur tafsir kontemporer, khususnya pemikiran M. Quraish Shihab dan Yusuf al-Qaradawi, serta artikel ilmiah yang ditelusuri melalui Google Scholar dengan kata kunci musyawarah, etika organisasi, dan manajemen perpustakaan, yang dibatasi pada publikasi lima tahun terakhir. Analisis dilakukan menggunakan teknik analisis tematik untuk mengidentifikasi nilai-nilai normatif serta relevansinya dalam konteks kelembagaan. Hasil penelitian menunjukkan bahwa musyawarah mengandung prinsip partisipasi inklusif, keadilan deliberatif, amanah, dan tanggung jawab kolektif yang dapat dioperasionalkan dalam perencanaan program, pengembangan koleksi, dan evaluasi layanan. Penelitian ini memberikan kontribusi secara teoretis dengan merumuskan musyawarah sebagai kerangka etika organisasi berbasis nilai-nilai Islam, serta secara praktis menyediakan landasan normatif bagi tata kelola perpustakaan yang partisipatif dan akuntabel.